Blended Learning in National Educational Policy 2020: Towards ending privileges to Higher Education - Garg, Suresh; Sharma, Ramesh Chander (Indian Journal of Educational Technology, 2022)
The National Education Policy 2020 of the Government of India is an exemplary milestone in the history of education in the country. It has proposed radical transformations in the education system in various dimensions, be it educational levels, pedagogy, infrastructure, training, and adoption of technology. Two revolutions have impacted deeply all our walks of life: the 4th industrial revolution where the artificial intelligence enabled technologies are transforming the way almost all functions and the 4th educational revolution (as proposed by Sir Anthony Seldon in his famous book pondering ‘Will Artificial Intelligence liberate or infantilise humanity?’). National Education Policy 2020 in clause 24.3 highlights the significance of blended learning for its impact on “social, affective, and psychomotor dimensions of learning”. This paper discusses the transition to and the pedagogy of blended learning in the context of National Education Policy 2020 towards closing the digital divide in higher education in India.